Anemia and its association with the weight of the newborn in pregnant teenagers: Myth or reality? - Arango-Ochante, Pedro M (2019)
Objective. To determine the relationship between maternal hemoglobin of pregnant adolescents and the weight of newborns in the National Maternal Perinatal Institute (INMP). Material and methods. 914 pregnant women were analyzed cross-sectionally by inclusion and exclusion criteria of 2729 deliveries of adolescents attended in the INMP corresponding to the year 2017. The data were collected from the birth registry and clinical histories, the variables of interest were hemoglobin maternal and the weight of the newborn. Results. Of the 914 births, 299 mothers (32%) presented anemia and 615 (68%) did not present anemia, the predominant age group were adolescents in the late stage 73% (with anemia) and 71% (without anemia). In the prenatal control, there was a predominance of insufficient or uncontrolled 74% (with anemia) and 73% (without anemia). Single women were the majority group, 91% (with anemia) and 93% (without anemia). The origin of the districts with quintiles IV and V was 90% (with anemia) and 87% (without anemia). No association was found between the weight of the newborn and the hemoglobin of the third trimester of the mother (Pearson's r = -0.0141, p-value = 0.6702). Conclusions. We did not find a relationship between low maternal hemoglobin and birth weight at term pregnancies of adolescents, this could be due to the fact that in the control of fetal weight there would be multiple factors that could be more influential in this group of pregnant adolescents.